2012
DOI: 10.1179/1743284712y.0000000044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short duration tempering on the microstructure and mechanical properties of a continuously annealed dual phase steel

Abstract: The effect of short duration tempering on the microstructure and mechanical properties of a continuously annealed dual phase steel was investigated using techniques like electron microscopy, dilatometry and thermodynamic calculations. It was found that a complex interplay of phenomena like tempering of martensite, quench aging of ferrite and recovery of the overall structure was responsible for the change in mechanical properties recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…[36] It can be seen that the obtained Q value of 108.8 kJ/mol is close to 103 kJ/mol, which implies that the tempering kinetics in this steel is controlled by carbon diffusion. This is consistent with the previous reports [37] and shows this effect quantitatively.…”
Section: Methodssupporting
confidence: 94%
“…[36] It can be seen that the obtained Q value of 108.8 kJ/mol is close to 103 kJ/mol, which implies that the tempering kinetics in this steel is controlled by carbon diffusion. This is consistent with the previous reports [37] and shows this effect quantitatively.…”
Section: Methodssupporting
confidence: 94%
“…When the peak temperature and holding time of higher temperature decrease, the martensite tempering of dual phase steels becomes less severe and thus the extent of softening decreases. 17, 34 Therefore, the local cooling could contribute to the reduction in the HAZ softening for both DP980 and DP780 joints.…”
Section: Resultsmentioning
confidence: 99%
“…Mukherjee et al [211] found that the tempering with a short duration noticeably affected the mechanical properties of DP steels. They reported that the yield strength of tempered DP steel increased primarily because of the quench aging of ferrite, while the decrease in tensile strength of steel was attributed to the tempered martensite.…”
Section: Temperingmentioning
confidence: 99%